Algae and Type 2 Diabetes: New Treatment Strategies - N. N. Besednova; S. P. Ermakova; T. A. Kuznetsova; I. D. Makarenkova; S. P. Krizhanovsky; B. G. Andryukov; T. S. Saporozhets (Антибиотики и Химиотерапия, 2020)
The review contains recent materials on the effects of extracts, polysaccharides, and polyphenols from brown algae in type 2 diabetes mellitus, which are a potential basis for creating effective antihyperglycemic agents. These biologically active substances are polyvalent biomodulators that have a multi-component effect in diabetes. These biopolymers reduce blood glucose levels, increase insulin production, decrease insulin resistance, inhibit α-amylase and α-glucosidase production, have antioxidant and anti-inflammatory activity, protect pancreatic, liver, and kidney tissues from high glucose concentrations. Algae are promising candidates for creating new generation drugs with associated activity, functional foods and dietary supplements for use in type 2 diabetes mellitus.